Cultural Studies Theory and Identity Construction in Popular Media Content - Ekpo Uduak Janet (Britain International for Academic Research (BIAR-Publisher), 2025)
The rise of digital media technologies has dramatically transformed how culture is created, shared, and understood. In Nigeria, platforms such as Instagram, TikTok, X, and YouTube have become key spaces where young people engage with popular media and cultural trends. These platforms are not just for entertainment they are places where identity is expressed, negotiated, and sometimes reshaped. This study argues that Nigerian youths increasingly see success through the lens of digital visibility, sometimes prioritizing online recognition over traditional markers like education or career achievements. Using a qualitative approach, this research examines social media trends, influencer culture, and reality TV narratives that dominate Nigeria’s digital space. Examples include Big Brother Naija, Pop the Balloon: The Game Hunt, and viral influencer content, illustrating how ordinary people can achieve public recognition rapidly. Findings show that young people often equate success with online visibility, popularity, and digital influence. While social media offers opportunities for creativity and entrepreneurship, it can also create unrealistic expectations about fame and wealth. The study concludes that popular media plays a central role in shaping youth identity and emphasizes the need for media literacy to help audiences critically engage with digital content.